Qualidade do leite proveniente de tanques de expansão comunitários no estado de Alagoas, Brasil - Soares, Karla Danielle Almeida (2014)
Milk production and its trade has a prominent place in the Brazilian economy, for its high nutritional value is a widely consumed food, and due to its composition can serve as a means of several pathogenic microorganisms that pose risks to public health. The objective of this study was to evaluate the quality of milk from bulk tanks of community in the state of Alagoas, Brazil. 160 milk samples from tanks belonging to a Cooperative Milk Producers state were collected. Samples were acquired in the three meso state (Wasteland Alagoas, Alagoas and Eastern Hinterland of Alagoas). We conducted research Staphylococcus coagulase positive (SCP), coliforms at 45 ° C, the presence of Salmonella spp., Listeria spp., Aeromonas spp., Count psicotróficos and mesophilic. As well as somatic cell count (SCC), Total Bacterial Count (TBC) and residues of antibiotics. For SCP was observed that 78.3 % (94 /120) of the samples were negative and 10.83% (13/120) were above the limit set by European Community Regulation. Salmonella spp was observed. and Listeria spp. in all samples. Met Aeromonas spp. 28.7% (46 /160) of samples. Mesophilic microorganisms 15 % (24 /160) of the samples were within the standard required by the law, while 85 % (136 /160) were outside the limit of up to 600,000 CFU / mL. As for the micro-organisms psicotróficos top scores were found in the 5x106UFC/mL 41.9 % (67 /160) of samples. We did not detect the presence of antibiotic residues in measurable levels in milk. For CCS and CBT, 79.4 % (127 /160) and 32.5 % (52 /160) of the samples were within the standard set by IN 62. The conclusion to this study was that large amount of microorganisms in fresh milk, which compromises the quality of milk. There was a percentage of 67.5 % of non-compliance for CBT and this can result from poor storage conditions and temperature that milk is subjected. The absence of antibiotic is suitable for public health. It is suggested hygienic-sanitary measures to ensure the achievement of a product within the quality standards for the population.